Multiparasitism in the endangered marbled polecat (vormela peregusna): a case report - Neslihan ÖLMEZ; Nilgün AYDIN; Barış SARI; Gencay Taşkın TAŞÇI; Yunus KILIÇ; Ekin Emre ERKILIÇ; Burak BÜYÜKBAKİ (Kafkas Universitesi Veteriner Fakültesi Dergisi)
The marbled polecat (Vormela peregusna) is classified as an endangered species within the small mammal group. In this report a young, injured male marbled polecat was brought to the Wildlife Protection, Rescue, Rehabilitation Application and Research Center of Kafkas University from the Sarıkamış district. Ectoparasitic examination revealed a flea sample identified as Nosopsyllus fasciatus. Macracanthorhynchus sp., belonging to the phylum Acanthocephala, and Eimeria sp. were detected in the examination of the fecal samples collected from the animal. This is the first documented report of these parasites observed in marbled polecat from Türkiye.